‘With Great Power Comes Virtual Freedom’. A Review of the First Italian Case Holding That (Food-Delivery) Platform Workers Are Not Employees - Aloisi, Antonio (SSRN, 2018)
This dispatch concentrates on a review of the first Italian ruling on the legal status of six platform workers who demanded to be reclassified as employees of the food-delivery company Foodora. Last April, the Employment Tribunal of Turin rejected their claims on the basis of the freedom they enjoyed in deciding if and when to work and even to disregard previously agreed shifts. The case note is organised as follows. Section I describes the main facts underlying the legal dispute, according to the judge’s description. Section II offers a context analysis of the Italian legal framework by clarifying the differences between the notions of employment and self-employment. Particular attention is paid to the most recent legislative interventions aimed at extending labour protections to independent workers whose personal activity is organised by the client. By arguing that the judge failed to consider the specificities of the digital work model, section III criticises the reasoning relying on a too narrow and formalistic understanding of the notion of subordination as well as the conclusive relevance attributed to the riders’ presumed flexibility. Section IV closes by summarising the main rulings decided in a set of European countries and providing some reflections on the possibility of applying the current legislation to platform worker. In sum, the dispatch advocates that, in order to properly classify the nature of the actual activity performed by platform workers, judges should assess the role of digital tools when it comes to organising, monitoring and disciplining the workforce, rather than merely focusing on discontinuity and flexibility that are key features of these non-standard work arrangements enabled by technology.
Keywords: Platform work; Foodora; Employment status; Misclassification; Italy; Food-delivery platform; On-demand economy; Gig-economy; Comparative labour law; Litigation; ODS 8 - Trabajo decente y crecimiento económico